SHRUB OF LILAC - Mamadaliyeva Sobira (International Journal of Innovations in Engineering Research and Technology, 2021)
Lilac (Syringa) is a flowering shrub that belongs to the Department of the angiosperms, dicotyledonous class, order anadivine, the family of oleaceae, in the genus Syringa.